The Influence of Content Marketing and Online Customer Reviews on Purchasing Decisions for Nivea Hand & Body Lotion on The TikTok Platform (Case study on Students of Management Department of Medan State University Class of 2021) - Naibaho, Histi Trifesi; Fikri, Miftah El (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
Skin care using hand & body lotion is an important step in maintaining skin moisture, one of which is by using Nivea products. However, based on Top Brand Index data, Nivea has experienced a decline in purchasing decisions from year to year. This study aims to analyze the effect of Content Marketing and Online Customer Reviews on purchasing decisions for Nivea Hand & Body Lotion on the TikTok platform, especially for students of the Management Department, State University of Medan, Class of 2021. The research method uses a descriptive quantitative approach with a simple linear regression technique, analyzed using SPSS 21. The results of the study show that Content Marketing and Online Customer Reviews partially and simultaneously have a positive and significant effect on purchasing decisions. These findings show the importance of digital strategies in shaping consumer perceptions and buying interests in the social media era. Therefore, companies need to continue to develop attractive marketing content and encourage positive reviews from consumers to increase the effectiveness of digital promotions.